Música entre nós - Barros, Larissa Gomes [UNESP]; Lima, Jairo Salim Pinheiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The "Music entre nós” project was born in 2003 and offers music courses for students and Unesp servers, their family and people in the community. The classes are taught by students of Unesp. The interest is the cultural interaction and the educational and personal development.

O projeto “Música entre nós” nasceu em 2003 e oferece cursos de música para unespianos, seus familiares e pessoas da comunidade. As aulas são ministradas por alunos da Unesp. O interesse é a interação sociocultural e o desenvolvimento didático e pessoal dos participantes.
Keywords: Musical theory and practice; Education; Teoria e prática musical; Educação